2012
DOI: 10.1111/j.1365-2796.2012.02588.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting T‐cell migration in inflammatory bowel disease

Abstract: Abstract. Marsal J, Agace WW

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 204 publications
(238 reference statements)
0
53
0
Order By: Relevance
“…A recent review evaluated the safety and efficacy of vedolizumab for the treatment of CD, and it was concluded that vedolizumab is an effective and well-tolerated drug [287]. Though it does not increase the risk of infection, it was demonstrated that vedolizumab may reduce the number of Treg cells and consequently their suppressive effect on colonic inflammation (see review [288]). …”
Section: Inhibition Of Cell Adhesionmentioning
confidence: 99%
“…A recent review evaluated the safety and efficacy of vedolizumab for the treatment of CD, and it was concluded that vedolizumab is an effective and well-tolerated drug [287]. Though it does not increase the risk of infection, it was demonstrated that vedolizumab may reduce the number of Treg cells and consequently their suppressive effect on colonic inflammation (see review [288]). …”
Section: Inhibition Of Cell Adhesionmentioning
confidence: 99%
“…The two most common types are Crohn disease (CD) and ulcerative colitis (UC). The inciting agent and exact underlying mechanism of IBD are not entirely known; however, convincing evidence suggests that it is mediated by abnormal T cell function in genetically susceptible individuals (1,2). Extraintestinal manifestations of IBD are not uncommon and probably reflect systemic inflammation, autoimmune susceptibility, metabolic and nutritional derangement, or drug-related toxicity (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…However, perhaps because of antagonizing α4β1, which mediates lymphocyte homing into the brain (Haanstra et al, 2013), natalizumab was associated with an increased risk of progressive multifocal leukoencephalopathy (Clifford et al, 2010). In contrast, this serious adverse event has not been reported in subjects receiving therapeutic modalities that specifically target T cell gut homing for the treatment of IBD (Marsal and Agace, 2012). These therapies include vedolizumab, a humanized antibody specific for the α4β7 dimer ( Feagan et al, , 2008; PF-00547-659, a fully human antibody against MAdCAM-1 ; etrolizumab, a humanized antibody against integrin subunit β7 (Marsal and Agace, 2012); and a small molecule CCR9 antagonist (CCX282, traficet-EN) (Keshav et al, 2013;Villablanca et al, 2011a).…”
Section: Targeting Lymphocyte Trafficking As a Therapeutic Strategymentioning
confidence: 76%
“…IBD might develop as a result of exaggerated T cell responses or inadequate regulatory pathways. Consistent with this view point, polymorphisms in IL-23R, STAT3, IL-21, IL-2, IL-2R, IL-7R, IL-10, and JAK2 loci (Khor et al, 2011) have been associated with IBD (Marsal and Agace, 2012).…”
Section: Inflammatory Bowel Disease As a Disease Of The Gastrointestimentioning
confidence: 79%
See 1 more Smart Citation